Implementation of Environmental Awareness Through Ecopedagogic Approach to Environmental Issues Elementary Schools - Nugroho, Hari; Winarno, Winarno (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
This research is motivated by the low level of student awareness in maintaining cleanliness in the school environment, where they assume that school cleaning is the responsibility of janitors. The focus of this research is to: 1) Identify the level of environmental awareness among elementary school students; 2) Identify factors that inhibit environmental awareness among elementary school students; 3) Evaluate the impact of the eco-pedagogical approach through environmental issues around students. This research used descriptive qualitative method. The research subjects were students, teachers, principals, and janitors, while the research object was the approach to environmental education through environmental issues around students. The data collection techniques used include observation, interview, and questionnaire. Observation sheets, interview guides, and questionnaire sheets were used as research instruments. The results obtained from this study are: 1) Increased environmental awareness among elementary school students; 2) Finding solutions to foster environmental awareness among elementary school students. 3) Developing an environmental awareness character education model among elementary school students. It can be concluded that bad habits related to the low environmental care attitude of students can be overcome by the school by making activities or habituation programs for environmental care.